Analyzing the risks embedded in option prices with rndfittool - Andre Barletta; Paolo Santucci de Magistris (Risks, 2018)
This paper introduces a new computational tool for the analysis of the risks embedded in a set of prices of European-style options. The software enables the estimation of the risk-neutral density (RND) from the observed option prices by means of orthogonal polynomial expansions. Orthogonal polynomials offer a viable alternative to more standard techniques based on interpolation and estimation of the second-order derivatives of option prices. The app rndfittool is available on GitHub and its usage is illustrated with examples based on real data.
Keywords: 330; European options; risk-neutral density; MATLAB app